2018
DOI: 10.1159/000491031
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genetics of the Human Neutrophil Antigens

Abstract: Background and Objective: Antibodies to human neutrophil antigens (HNAs) have been implicated in transfusion-related acute lung injury and allo- and autoimmune neutropenia. To date, five HNA systems are assigned, and during the last decades enormous efforts have been undertaken to identify the underlying genes and to characterize the antigens. This review of the literature will provide the current genetic, molecular and functional information on HNAs. Recent Findings: New information on alleles and antigens ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 99 publications
1
50
0
Order By: Relevance
“…The Fc γ-receptor IIIb glycoprotein (FcγRIIIb; also CD16b) comprises the HNA-1a, -1b, -1c and -1d alloantigens and is important in immune complex clearance and phagocytosis of opsonised microorganisms. 25 The majority of NAIN cases have demonstrated alloantibodies against HNA-1a, -1b and -2a. 5,6 However, alloantigens HNA-1c, -1d, -3a, -3b, -4a, -4b and -5a and their respective antibodies have also been reported in NAIN.…”
Section: Discussionmentioning
confidence: 99%
“…The Fc γ-receptor IIIb glycoprotein (FcγRIIIb; also CD16b) comprises the HNA-1a, -1b, -1c and -1d alloantigens and is important in immune complex clearance and phagocytosis of opsonised microorganisms. 25 The majority of NAIN cases have demonstrated alloantibodies against HNA-1a, -1b and -2a. 5,6 However, alloantigens HNA-1c, -1d, -3a, -3b, -4a, -4b and -5a and their respective antibodies have also been reported in NAIN.…”
Section: Discussionmentioning
confidence: 99%
“…The sample set included gene CNVs from zero up to four copy samples for HNA-1. 43 HNA-2 phenotypes were determined for five (four positive, one negative) samples by flow cytometry 22 using an APC-labeled mem166 clone (Santa Cruz Biosciences).…”
Section: Sample Selection For Sequencingmentioning
confidence: 99%
“…The frequency of the HNA‐2 null phenotype has been reported to be approximately 0.5% to 5% among Thai and other populations . HNA‐2 isoantibodies produced by HNA‐2 null individuals are implicated in transfusion‐related acute lung injury (TRALI) and immune neutropenia …”
Section: Introductionmentioning
confidence: 99%
“…9,10 HNA-2 isoantibodies produced by HNA-2 null individuals are implicated in transfusion-related acute lung injury (TRALI) and immune neutropenia. 3,5 To date, different mutations of HNA-2 antigen expression have been reported in varying populations. 1,8,14 A recent study in a Chinese population identified two polymorphisms associated with the HNA-2 null phenotype in exons 7 and 8 of the CD177 gene (c.787A>T and c.955delG, respectively).…”
Section: Introductionmentioning
confidence: 99%